A study to determine minimum effective dose of oxytocin infusion during caesarean delivery in parturients at high risk of uterine atony - Shashikiran; Harsimran Kaur; Renu Bala; Neha Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Oxytocin, a commonly used drug to prevent uterine atony after caesarean section, should be administered as dilute rapid infusion rather than as a bolus. This study was conducted to calculate ED90 of oxytocin infusion during caesarean delivery in parturients at high risk of postpartum haemorrhage (PPH). Materials and Methods: One hundred and twenty parturients having one or more risk factors for PPH received a blinded infusion of oxytocin following emergency caesarean delivery. The initial dose of oxytocin infusion was started as 0.4 IU min−1. The dose of oxytocin infusion for the next parturient was based on the response of preceding patient in increments or decrements of 0.1 IU min−1 as per a biased-coin design up-down sequential method (UDM). Measurements of non-invasive blood pressure and heart rate were taken at 2 min intervals from the time of oxytocin infusion. Intraoperative blood loss was noted. Side effects such as tachycardia, hypotension, nausea, vomiting, chest pain, headache and flushing were also recorded. Results: The ED90 of oxytocin infusion was found to be 0.405 IU min−1 (95% confidence interval 0.3864-0.4125) as calculated by Firth's penalised likelihood estimation using a biased-coin design UDM. Hypotension was observed for brief period of time in 25.6% of parturients and brief period of tachycardia was observed in 9.4% of parturients. No headache, flushing, chest pain and vomiting were observed in any parturients in our study. The estimated blood loss was within the normal limits. Conclusion: Our study showed that ED90 of oxytocin infusion required to achieve adequate uterine tone (UT) after an emergency caesarean delivery in parturients at high risk of uterine atony was 0.405 IU min−1. The higher doses of oxytocin did not result in further improvement of UT. Therefore, early use of alternative uterotonic therapy is preferable to achieve adequate UT.